Diversity of butterflies (Lepidotera, Papilionidae) in some forest areas of Vietnam - Lien, Vu Van (Academia Journal of Biology, 2012)
Study on diversity of Papilionidae butterflies was carried out in 10 different National Parks, Nature Reserves and other forest areas (from sea level to the highest peak of Vietnam 3143m and from inland to islands) Hoang Lien and Van Ban (Lao Cai), Ba Be (Bac Can), Tam Dao (Vinh Phuc), Cat Ba (Hai Phong), Cuc Phuong (Ninh Binh), Minh Hoa (Quang Binh), Ngoc Linh (Kon Tum), Hon Ba (Khanh Hoa) and Phu Quoc (Kien Giang) from 1997 to 2008. Butterflies were collected opportunity at different habitats and elevations to make comprehensive lists for areas. Similarity index (Cluster analysis) was used to compare the similarity of butterfly compositions between studied areas. Total of 59 butterfly species of Papilionidae were recorded, of which 4 species are listed in CITES which are Teinopalpus imperialis, T. aureus, Troides helena and T. aeacus, Two species of Teinopalpus and four other species (Meandrusa sciron, Graphium phidias, Atrophaneura crassipes and Papilio noblei) are listed in IUCN. Hoang Lien national park has the most species diversity. Some species found in studied areas only distribute in Hoang Lien such as Byasa letterllei, Papilio krishna, P. machaon, P. xuthus and Graphium leechi. Some species of Vietnam only are found in Hoang Lien such as Byasa latreillei and Papilio krishna. Similarity of butterfly composition is highest between Tam Dao and Cuc Phuong. There are 9 pairs of studied areas with similarity of species composition more than 70% are Hoang Lien - Van Ban, Van Ban - Tam Dao, Ba Be - Tam Dao, Ba Be - Cuc Phuong, Ba Be - Cat Ba, Ba Be - Minh Hoa, Tam Dao - Cuc Phuong, Cat Ba - Cuc Phuong, and Cuc Phuong - Minh Hoa. Species composition of Hoang Lien is rather similar with species composition of Van Ban. The similarity of species composition is low between Hoang Lien and Hon Ban, between Van Ban and Phu Quoc and lowest between Hoang Lien and Phu Quoc (24%) where two areas are greatly different in geography and altitudes. The result indicated that geography-climate and altitude are factors deciding the similarity of butterfly compositions between areas.